Feature Acquisition System of Protection and Control Equipment Based on IoT Agent - GAN Yunhua; ZHAO Lanying; ZOU Zhiyang; LI Linfeng (Kongzhi Yu Xinxi Jishu)
This paper proposes a feature acquisition system based on IoT agent for protection and control equipment in substations, addressing the limitations of monitoring methods and incomplete data caused by the integration of condition monitoring functions in such equipment. The system, which integrates protection and control equipment, data aggregation gateways, and health management backends, enables real-time monitoring of equipment operating parameters and state evaluation. By deploying internal feature acquisition modules, designing the hardware and software architecture of the data aggregation gateway, and employing analogy-based discrimination and fault prediction evaluation methods, the effectiveness of the system has been verified. The research results indicate that this system can provide scientific basis for operation and maintenance, thereby enhancing the intelligence level of equipment management.